Cost Effective Options for Greenhouse Gas (GHG) Emission Reduction in the Power Sector for Developing Economies — A Case Study in Sabah, Malaysia - Stella Morris; Yun Seng Lim; Siong Lee Koh (Energies, 2011)
With their increasing shares of global emissions developing economies are increasingly being pressured to assume a greater role in global greenhouse gas (GHG) emission reduction. Developed countries have invested tremendously in and proclaimed renewable energy (RE) and associated smart power technologies as solutions to meet their energy demands and reduce their GHG emissions at the same time. However, in the developing economies, these technologies may not deliver the desired results because they have their unique characteristics and priorities, which are different from those of the developed world. Many GHG emission reduction technologies are still very expensive and not fully developed. For the developing economies, the adoption threshold may become very high. Therefore, the cost effectiveness and practicality of each technology in reducing GHG emission in the developing economies may be very different from that of the developed economies. In this paper, available RE and other GHG emission reduction technologies are individually considered in a case study on Sabah, one of the 13 states in Malaysia, in order to assess the effects of the individual technologies on GHG emission and electricity cost reductions.